Vertical UWB CDM antenna with integrated band notched filtering - S. A. , Hamzah (IEEE, 2007)
A compact vertical circular disc monopole (CDM) antenna with U-shape slot and inverted U – shape slot (radius, a=1.5cm, thickness, t=0.02cm, height gap, h=0.01cm and the ground plane size of 14cm2) is presented in this paper. The CDM antenna has been reported to yield wide-impedance bandwidth, good radiation efficiency and one of the best candidates for ultra wide band (UWB) antenna system. The antenna was designed and simulated by using CST software and copper is used as the material. The designed antennas satisfy the -10 dB return loss requirement in the frequency band between 2GHz – 10 GHz, while showing the band stop characteristic in the frequency band of 5 GHz.